Legal Construction of Government Agency Asset Certification Regarding Land Rights Formerly Under Dutch Control - Mahendra, Jacki; Masykur, Mohammad Hamidi; Sjafi'i, R. Imam Rahmat (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
An important aspect of optimal management of state assets includes aspects of securing state assets. The form of state asset security measures can be through certification activities for land plots spread throughout the territory of Indonesia. Normatively,